2012
DOI: 10.4172/2161-0959.1000113
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Cinacalcet for the Treatment of Secondary Hyperparathyroidism in CKD Patients on Peritoneal or Hemo Dialysis: The Middle-East Experience

Abstract: Background: Management of secondary hyperparathyroidism is challenging with traditional therapy. The calcimimetic cinacalcet hydrochloride acts on the calcium-sensing receptors to increase its sensitivity to calcium, thereby reducing parathyroid hormone (PTH) secretion. Calcimimetics lower parathyroid hormone levels without increasing calcium and phosphorus levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…This breakthrough in the pharmacological management of SHPT has been corroborated in different population subgroup, including our previous study in the middle-east dialysis population, where once daily cinacalcet effectively decreased the PTH values in hemodialysis and peritoneal dialysis patients with SHPT [11].…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…This breakthrough in the pharmacological management of SHPT has been corroborated in different population subgroup, including our previous study in the middle-east dialysis population, where once daily cinacalcet effectively decreased the PTH values in hemodialysis and peritoneal dialysis patients with SHPT [11].…”
Section: Introductionmentioning
confidence: 54%
“…In our previous study, we have shown the effectiveness of cinacalcet therapy compared to conventional treatment in controlling SHPT in dialysis patients [11]. In the present study we had taken up the issue of a different dosing regimen of cinacalcet applicable to the same patient population.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation